The Longitudinal Flow of Oil and Petroleum Products in the Channels and Pipes - Tolchinsky, Yu. A.; Ved, V. E.; Zhantasov, M. K.; Satayev, M. I.; Saipov, A. A. (The Italian Association of Chemical Engineering, 2016)
A model associated fluid flow and heat transfer of longitudinal flows of oil in pipes and channelsis considered. The model is based on the existence of a solid core or two such cores and fluid flow part. The flow is considered for the fluid part of Newtonian fluid, for power-law fluidsand for a Newtonian fluid in a turbulent regime. The amendments related to the nonlongitudinal to the flow equations of fluid dynamics and heat transfer, and their impact on core characteristics arediscussed.